Conceptualizing the Impact of Workarounds – An Organizational Routines’ Perspective - Wolf, Verena; Beverungen, Daniel (Proceedings of the 27th European Conference on Information Systems (ECIS))
Employees’ acceptance and resistance of new technology and social structure are frequently examined in Information Systems research. Resistance is expressed in various forms, including a lack of cooperation, workarounds, and physical sabotage. Workarounds, in particular, have a dual nature and can refer to both, undesirable behavior that contradicts organizational struc-ture and to desired organizational innovation. While antecedents and different forms of worka-rounds have been explored, literature has remained silent on how and why workarounds of an individual employee can affect activities performed by other employees and thereby, change work routines on an organizational level. Since employees’ day-to-day performances constitute the ostensive patterns of a routine, we argue that workarounds will not only impact performanc-es of adjacent routines, but also transform the organization as a social structure. With a prelim-inary set of qualitative data from 24 interviews, we used a multiple case study design to concep-tualize six patterns that illustrate how and why workarounds can spread through an organiza-tion. The patterns are systematized by a framework that considers three types of collaboration and two types of handoffs across routines. This first evidence points at the nature of complex desired and undesired consequences that can emerge through workarounds performed in an organization.
Keywords: Resistance; Workaround; Organizational Routines; Structuration Theory